RUNX2 in mammary gland development and breast cancer1. Issue 6 (25th February 2013) - Ferrari, Nicola; McDonald, Laura; Morris, Joanna S.; Cameron, Ewan R.; Blyth, Karen
Abstract Runx2 is best known as an essential factor in osteoblast differentiation and bone development but, like many other transcription factors involved in development, is known to operate over a much wider tissue range. Our understanding of these other aspects of Runx2 function is still at a relatively early stage and the importance of its role in cell fate decisions and lineage maintenance in non‐osseous tissues is only beginning to emerge. One such tissue is the mammary gland, where Runx2 is known to be expressed and participate in the regulation of mammary specific genes. Furthermore, differential and temporal expression of this gene is observed during mammary epithelial differentiation in vivo, strongly indicative of an important functional role. Although the precise nature of that role remains elusive, preliminary evidence hints at possible involvement in the regulation of mammary stem and/or progenitor cells. As with many genes important in regulating cell fate, RUNX2 has also been linked to metastatic cancer where in some established breast cell lines, retention of expression is associated with a more invasive phenotype. More recently, expression analysis has been extended to primary breast cancers where high levels of RUNX2 align with a specific subtype of the disease. That RUNX2 expression correlates with the so called "Triple Negative" subtype is particularly interesting given the known cross talk between Runx2 and estrogen receptor signaling pathways. This review summaries our current understanding of Runx2 in mammary gland development and cancer, and postulates a role that may link both these processes. J. Cell. Physiol. 228: 1137–1142, 2013. © 2012 Wiley Periodicals, Inc.